Staphylococcus aureus bloodstream infection: a pooled analysis of five prospective, observational studies. - Kaasch, A; Barlow, G; Edgeworth, J; Fowler, V; Hellmich, M; Hopkins, S; Kern, W; Llewelyn, M; Rieg, S; Rodriguez-Baño, J; Scarborough, M; Seifert, H; et al. (2014)
OBJECTIVES: Staphylococcus aureus bacteraemia is a common, often fatal infection. Our aim was to describe how its clinical presentation varies between populations and to identify common determinants of outcome. METHODS: We conducted a pooled analysis on 3395 consecutive adult patients with S. aureus bacteraemia. Patients were enrolled between 2006 and 2011 in five prospective studies in 20 tertiary care centres in Germany, Spain, United Kingdom, and United States. RESULTS: The median age of participants was 64 years (interquartile range 50-75 years) and 63.8% were male. 25.4% of infections were associated with diabetes mellitus, 40.7% were nosocomial, 20.6% were caused by methicillin-resistant S. aureus (MRSA), although these proportions varied significantly across studies. Intravenous catheters were the commonest identified infective focus (27.7%); 8.3% had endocarditis. Crude 14 and 90-day mortality was 14.6% and 29.2%, respectively. Age, MRSA bacteraemia, nosocomial acquisition, endocarditis, and pneumonia were independently associated with death, but a strong association was with an unidentified infective focus (adjusted hazard ratio for 90-day mortality 2.92; 95% confidence interval 2.33 to 3.67, p < 0.0001). CONCLUSION: The baseline demographic and clinical features of S. aureus bacteraemia vary significantly between populations. Mortality could be reduced by assiduous MRSA control and early identification of the infective focus.